Sex differences in myocardial flow reserve among individuals with type 2 diabetes: insights from the DiaHeart study - Anne-Cathrine Skriver-Møller; Philip Hasbak; Ida K. B. Rasmussen; Martin B. Blond; Victor S. Wasehuus; Mats C. H. Lassen; Morten Lindhardt; Allan Kofoed-Enevoldsen; Urd L. Kielgast; Emilie H. Zobel; Jens P. Goetze; Lene Holmvang; et al. (Cardiovascular Diabetology)
Abstract Background Type 2 diabetes is a stronger risk factor for cardiovascular disease (CVD) in women compared with men possibly due to higher susceptibility to develop myocardial microvascular dysfunction. We investigated sex-dependent effects of risk factors on myocardial blood flow (MBF) and myocardial flow reserve (MFR) in individuals with type 2 diabetes without overt CVD. Methods Cross-sectional analysis of a prospective study including 901 individuals recruited between 2020 and 2023. All participants underwent a cardiac 82-Rubidium positron emission tomography/computed tomography scan to quantify MBF at rest and during pharmacologically induced stress, allowing for calculation of MFR. Linear regression, with/without interaction terms for sex, was used to test whether sex modified the association between MFR/MBF and risk factors. Results Mean (SD) age was 65 (8.9) years, diabetes duration was 14 (8.4) years, and 266 (29.5%) were women. Women had higher MBF at rest and stress but had lower MFR (mean (SD) 2.44 (0.67) vs. 2.59 (0.77), p = 0.003) than men. A similar proportion of men and women (21.1% vs. 23.7%) had an MFR < 2. The decline in predicted MFR with age differed between sexes. At age 55, women had a mean MFR that was 0.29 lower than men (95% CI: − 0.44 to − 0.14), but by age 75, this difference had nearly disappeared (− 0.04, 95% CI: − 0.19 to 0.11). However, after adjustment for other risk factors, the interaction between sex and age was not statistically significant (p = 0.057). No other risk factors exhibited significant sex-dependent interactions. Conclusions In individuals with type 2 diabetes without overt CVD, women exhibited lower MFR than men, primarily due to higher MBF at rest, suggesting sex-related differences. While MFR declined in both sexes, the sex difference was more pronounced in younger individuals and diminished over time. These findings underscore the need for further research into sex-specific thresholds for MFR in cardiovascular risk stratification. Graphical abstract